TRANSFORMASI PERAN GURU DARI PENGAJAR KE FASILITATOR BERBASIS PENDEKATAN HUMANISTIK - Nadzifah Aisyah Fauzi; Rahma Nafalina Azzahra; Septia Rosada; Amelia Gita Maharani; Nur Laila Ana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of education in the digital era requires changes in learning approaches that are more student-centered and humanistic. However, learning practices in schools are still often dominated by teacher-centered approaches, where teachers act as the primary source of knowledge and students tend to be passive. This study aims to analyze the transformation of teachers’ roles from instructors to facilitators based on a humanistic approach, identify challenges in its implementation, and examine strategies to support its effectiveness in learning. This research employed a qualitative approach with a literature study method by collecting secondary data from scientific journals, books, and relevant academic sources. Data were analyzed using content analysis through the identification, comparison, and synthesis of various theories and findings. The results indicate that the transformation of teachers into facilitators through a humanistic approach can create more meaningful, participatory, and student-centered learning. This approach contributes to improving students’ motivation, independence, critical thinking, and character development. However, its implementation still faces several challenges, including limited teacher understanding, inadequate training, and education systems that remain academically oriented. Therefore, support through teacher professional development and educational policies is necessary to optimize the implementation of humanistic learning.